2018
DOI: 10.1103/physrevb.97.104108
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance study of atomic hydrogen stabilized in solid neon below 1 K

Abstract: We report on an electron spin resonance study of atomic hydrogen stabilized in a solid Ne matrices carried out at a high field of 4.6 T and temperatures below 1 K. The films of Ne, slowly deposited on the substrate at the temperature ∼1 K, exhibited a high degree of porosity. We found that H atoms may be trapped in two different substitutional positions in the Ne lattice as well as inside clusters of pure molecular H2 in the pores of the Ne film. The latter type of atoms was very unstable against recombination… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 41 publications
8
9
0
Order By: Relevance
“…In our recent study [6], we found that the solid neon with small (well below 6%) admixtures of hydrogen forms a highly porous solid with small clusters of pure H 2 embedded inside the pores. We observed an exceptionally high recombination rate of H atoms in such H 2 clusters upon raising the temperature to 0.3-0.6 K, which could be explained by a solid-liquid transition in the clusters.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…In our recent study [6], we found that the solid neon with small (well below 6%) admixtures of hydrogen forms a highly porous solid with small clusters of pure H 2 embedded inside the pores. We observed an exceptionally high recombination rate of H atoms in such H 2 clusters upon raising the temperature to 0.3-0.6 K, which could be explained by a solid-liquid transition in the clusters.…”
Section: Introductionmentioning
confidence: 86%
“…In our recent study of H atoms in solid Ne:H 2 mixtures [6], we found that raising temperature from 0.1 to 0.3-0.6 K and admitting a superfluid He film into the sample Fig. 3 Spectrum of electrons trapped in the "pure" Ne Sample 1 (100 ppm H 2 ) after condensing He film into sample cell.…”
Section: Effect Of Unsaturated Helium Film and Annealingmentioning
confidence: 99%
See 2 more Smart Citations
“…Clusters of a greater size can also be prepared by annealing hydrogen films quench condensed onto a cold substrate [11,12]. In our recent study [13], we observed that a large number of such small molecular hydrogen clusters can be accommodated in a porous matrix of quench condensed solid neon films. In addition, an exceptionally high recombination rate of H atoms in such H 2 clusters at temperatures 0.3-0.6 K provided evidence for a solidliquid transition in H 2 clusters predicted for solid H 2 in a restricted geometry [6].…”
Section: Introductionmentioning
confidence: 95%